Rare intronic mutation between Exon 62 and 63 (c.9225–285A>G) of the dystrophin gene associated with atypical BMD phenotype - Schüssler, S. C.; Gerhalter, T.; Abicht, A.; Müller-Felber, W.; Nagel, Armin Michael; Trollmann, Regina (Neuromuscular Disorders, 2020)
Dystrophinopathies are predominantly caused by deletions, duplications and point mutations in the coding regions of the dystrophin gene with less than 1% of all pathogenic mutations identified within intronic sequences. We describe a 17-year-old male with a Becker muscular dystrophy diagnosis and mental disability due to an intron mutation that led to aberrant splicing and formation of an additional exon. Histopathological analysis of muscle tissue revealed signs of muscular dystrophy and reduced signal for dystrophin, alpha-sarcoglycan, and alpha-dystroglycan. Multiplex ligation-dependent probe amplification screening and total sequencing of the dystrophin gene did not identify a mutation in the coding regions. However, next generation sequencing revealed an intron mutation between exons 62 and 63 of the dystrophin gene known for pseudoexon formation and disruption of the reading frame. We report a functional consequence of this mutation as an increased intracellular-weighted sodium signal (assessed by 23Na-magnetic resonance imaging) in leg muscles.
CRIS-Team Scopus Importer:2020-08-28
Keywords: 23Na-MRI; Aberrant splicing; Becker muscular dystrophy; Dystrophin; Intracellular-weighted sodium signal; Next generation sequencing